Pengaruh Financial Distress dan Capital Expenditure Terhadap Nilai Perusahaan - Fitria Ciptaningrum, (2021)
This study aims to determine the influence of financial distress and capital expenditure on the value of non-financial state-owned companies listed on the Indonesia Stock Exchange for the period 2015-2019. This research uses a quantitative approach of secondary data in the form of financial statements and annual reports of companies. This study used a sample of 95 non-financial state-owned companies through purposive sampling method. Data analysis is conducted through regression model selection test, classic assumption test, panel data regression, and hypothesis test using STATA version 16. The results showed that: (1) financial distress has a significant negative effect on firm value, (2) capital expenditure has no significant effect on firm value, and variable control (3) institutional ownership has no significant effect on firm value.